1998
DOI: 10.1080/1350462980040103
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Views about What to do about Sustainable Development

Abstract: In its various guises the political and economic implications of the spectrum of ideas labelled 'sustainable development' have been widely discussed in the media. This research engaged secondary school teachers in the debate concerning the implications for education of the concept of sustainable development. Underpinning this pilot research project is the assumption that teachers, as generally informed citizens, have been sensitised to some of the issues raised in the public domain. Teachers in both the USA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Brooks (2006Brooks ( , 2010 also suggested that what teachers valued about geography had implications for how they designed the classroom curriculum. Similarly, other studies have also noted that teachers in the United States and Scotland (Cross, 1998) and preservice teachers in Australia (Gooch, Rigano, Hickey, & Fien, 2008) were reluctant to explicitly advocate for the environment in their lessons. On the other hand, large-scale quantitative surveys of geography teachers from 18 different countries (Ballantyne, 1999), from the United Kingdom (Grace & Sharp, 2000;Tomlins & Froud, 1994), and across the United Kingdom and Hong Kong (Lee, 1993) indicate that teachers feel responsible for the promotion of positive environmental attitudes and behaviors.…”
Section: Teaching Controversial Issuesmentioning
confidence: 96%
“…Brooks (2006Brooks ( , 2010 also suggested that what teachers valued about geography had implications for how they designed the classroom curriculum. Similarly, other studies have also noted that teachers in the United States and Scotland (Cross, 1998) and preservice teachers in Australia (Gooch, Rigano, Hickey, & Fien, 2008) were reluctant to explicitly advocate for the environment in their lessons. On the other hand, large-scale quantitative surveys of geography teachers from 18 different countries (Ballantyne, 1999), from the United Kingdom (Grace & Sharp, 2000;Tomlins & Froud, 1994), and across the United Kingdom and Hong Kong (Lee, 1993) indicate that teachers feel responsible for the promotion of positive environmental attitudes and behaviors.…”
Section: Teaching Controversial Issuesmentioning
confidence: 96%
“…This conclusion is supported by teachers who have expressed concerns about the negative effects on students of teaching about environmental disasters (Cross, 1998;Hicks, 2002;Christenson, 2004). However, there seems to be an additional implicit assumption that adopting a positive orientation means that students will become (or at least more likely to become) motivated to learn about and take actions to improve the environment.…”
Section: Environmental Education and The Problem Orientation Concernmentioning
confidence: 99%
“…Of course, as evidenced in Smyth's later report on the failure to implement a national ESD strategy in Scotland (Lavery & Smyth, 2003), non-rational political factors can play a major role in environmental education policy decisions. So, while rationality alone cannot account for most environmental and educational decisions, environmental education processes need not exclude the consideration of non-rational factors; however, there is often a tendency for educators to do so, for example, K-12 teachers avoiding political dimensions (Cross, 1998), and university teachers, especially perhaps scientists, steering clear of the spiritual.…”
Section: Environmental Education and The Problem Orientation Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Petergem et al (2007) illustrated, teachers lack insight into the complexities of EE issues and how their teaching might contribute to productive EE. Previous researches also showed that most teachers are unaware of the underlying theoretical issues concerning EE and the concept of sustainable development (Cross, 1998;Summers, Kruger, and Childs, 2000). EE requires special training and commitment because it needs a different focus and outlook that many prospective teachers have not experienced in their own education (Tilbury, 1997).…”
mentioning
confidence: 99%